Cell biology a short course - Bolsover, Stephen R. 1954-
"This text tells the story of cells as the units of life in a colorful and student-friendly manner, taking an "essentials only" approach. By using the successful model of previously published "Short Courses," this text succeeds in conveying the key points without overburdening the reader with secondary information. The authors skillfully present concepts by illustrating them with clear diagrams and examples from current research. Special boxed sections focus on the importance of cell biology in medicine and industry today. This text is completely updated from the successful "Cell Biology, A Short Course, 3e," includes new chapters"--Provided by publisher.